Public Relations and Issues of Technological Progress: Communicating the Benefits and Risks of AI and IoT to the Public - Juwita, Rina; Nurhayai, Nurhayai; Syaras, Dang; Rintaningrum, Ratna; Herliani, Ade (Journal International Dakwah and Communication, 2024)
In an era of rapid technological progress, the presence of artificial intelligence (AI) and the Internet of Things (IoT) has an impact on society. However, along with the benefits, there are also risks and concerns regarding privacy, security and unemployment due to automation. In this context, the role of public relations becomes crucial in communicating accurate and balanced information to the public about the benefits and risks of AI and IoT. This research aims to explore the role of public relations in communicating the benefits and risks of AI and IoT to the public. The main focus is to understand how public relations practitioners can manage effective and transparent messages to form balanced perceptions and deep understanding among the public. The research method used is literature analysis and case studies to understand best practices in public communication about AI and IoT. Interviews with public relations practitioners were also conducted to gain direct insight into strategies and challenges in communicating complex technology issues to the public. The results of this research identify that public relations plays an important role in conveying accurate, clear and trustworthy information about the benefits and risks of AI and IoT to the public. Effective strategies include a narrative-based approach, use of relevant media platforms, and active engagement with stakeholders. The research conclusion is that by implementing best practices in public relations, organizations and institutions can help society to fully understand the impact of AI and IoT. Transparent and open communication can strengthen public trust and minimize unwarranted fears, thereby creating wider acceptance of technological advances.